The Relationship Between Individual Factors and Work Environment Factors with Work Stress in Workers in the Residue Catalytic Cracking Complex (RCC) Area of PT Kilang Pertamina Internasional (Persero) Refinery Unit VI Balongan - Nabila Gustin Eka Nur Rahmah; Anik Setyo Wahyuningsih (Jurnal Kesmas Prima Indonesia, 2025)
The significant work stress trend in the RCC Complex Area, with a percentage in May 2022 of 55.56% in the RCU Unit and 66.67% in the LEU Unit experiencing severe stress which then in June 2023 strengthened this finding where 13.3% of workers experienced high stress and 10% experienced very high stress indicating an urgent need for intervention strategies to overcome stress in the work environment. This study aims to determine the relationship between individual factors and work environment factors on work stress in the RCC Complex Area. The type of research used is an analytical quantitative method with a cross-sectional approach. The sample set was 73 respondents with a purposive sampling technique. The instruments used were the Perceive Stress Scale (PSS) questionnaire and a sound level meter noise measuring device. Data were analyzed using Chi-Square analysis. Based on the Chi-Square test of the Relationship Between Individual Factors and Work Environment Factors with Work Stress in Workers in the RCC Complex Area of ​​PT Kilang Pertamina Internasional (Persero) RU VI Balongan, the results showed that those that had a relationship with work stress (p<0.05) were age (p=0.000), length of service (p=0.016), level of education (p=0.002), and noise (p=0.001). While those that were not related to work stress were marital status (p=0.573). From the results of this study, it can be concluded that there is a significant relationship between age, length of service, level of education, noise with work stress in workers in the RCC Complex Area of ​​PT Kilang Pertamina Internasional (Persero) RU VI Balongan. Tren stress kerja yang berlangsung signifikan pada Area RCC Complex, dengan presentase pada bulan Mei 2022 sebanyak 55,56% di Unit RCU dan 66,67% di Unit LEU mengalami stres berat yang kemudian pada bulan Juni 2023 memperkuat temuan ini dimana 13,3% pekerja mengalami stres tinggi dan 10% mengalami stres sangat tinggi menunjukkan kebutuhan mendesak untuk strategi intervensi guna mengatasi stres di lingkungan kerja tersebut. Penelitian ini bertujuan untuk mengetahui hubungan antara faktor individu dan faktor lingkungan kerja terhadap stress kerja di Area RCC Complex. Jenis penelitian yang digunakan adalah metode kuantitatif analitik dengan pendekatan cross sectional. Sampel yang ditetapkan sebesar 73 responden dengan teknik purposive sampling.  Instrumen yang digunakan adalah kuesioner Perceive Stress Scale (PSS) dan alat pengukur kebisingan sound level meter. Data dianalisis menggunakan analisis Chi-Square. Berdasarkan uji Chi-Square Hubungan Antara Faktor Individu dan Faktor Lingkungan Kerja dengan Stres Kerja pada Pekerja di Area RCC Complex PT Kilang Pertamina Internasional (Persero) RU VI Balongan diperoleh hasil bahwa yang memiliki hubungan dengan stres kerja (p<0,05) adalah usia (p=0,000), masa kerja (p=0,016), tingkat pendidikan (p=0,002), dan kebisingan (p=0,001). Sedangkan yang tidak berhubungan dengan stres kerja adalah status pernikahan (p=0,573). Dari hasil penelitian ini dapat disimpulkan bahwa ada hubungan yang signifikan antara usia, masa kerja, tingkat pendidikan, kebisingan dengan stres kerja pada pekerja di Area RCC Complex PT Kilang Pertamina Internasional (Persero) RU VI Balongan.